Design of IoT-Based Aquaculture Water Quality Parameter Monitoring System - Chen, Weiheng; Wang, Mingwu; Liao, Xiaozhou; Wu, Zedong (2023 IEEE 16th International Conference on Electronic Measurement & Instruments (ICEMI), 2023)
Traditional water quality monitoring in aquaculture in China is mainly done manually, which is not only time-consuming and labor-intensive, but also has low accuracy and is gradually being phased out by the market. To address the above-mentioned issues, the author has developed an aquaculture water quality parameter monitoring system using the Internet of Things. The system mainly consists of sensor modules, A/D conversion circuits, microcontrollers, and display terminals. Sensors such as pH value, conductivity, temperature, and dissolved oxygen are arranged at underwater nodes. Each sensor has a built-in conditioning circuit, which can convert the real-time collected parameter values into digital quantities through the A/D module. The network layout of the main station sensor and the sub-station using the STM32F103 microcontroller is constructed. The main station uses a master-slave mode to poll the sub-stations for data, and the data is collected and aggregated to mobile apps or remote computers and other monitoring terminals for processing and display through the 4G DTU wireless module. Research shows that the system has the characteristics of wide coverage, high real-time performance, remote monitoring and alarm, and has high practical application value.